Parallel and distributed algorithms - Aupy, Guillaume; Tang, Xueyan (Concurrency and Computation: Practice and Experience, 2018)
Summary We introduce the papers submitted to the special issue of Computation, Concurrency: Practice and Experience on parallel and distributed algorithms.